The evolution of health education in Brazil and the reference unit in rehabilitation as a scenario of academic practice in occupational therapy: a narrative review (Research, Society and Development, 2022)
Teaching and assistance are elements of undergraduate courses in the health area. The challenge is how they can be articulated to contribute to the process of training the student as a future professional, who is committed to developing quality work, with resolution and humanization, especially in services linked to the Unified Health System (SUS) . The study presents aspects about the evolution of health education in Brazil, and more specifically, Occupational Therapy, and its relationship with a rehabilitation unit linked to the University of the State of Pará (UEPA), called Unit of Rehabilitation in Physiotherapy and Occupational Therapy (UEAFTO). For this, a narrative review was carried out, from February to May 2022, in the Medical Literature Analysis and Retrieval System Online (MEDLINE), Virtual Health Library (BVS), Scientific Electronic Library Online (SCIELO) and Google databases. Academic, as well as reading and analysis of bibliographic references of the discipline “The SUS as a School” (curricular component of the Postgraduate Program in Health Education in the Amazon - Professional Master's Degree, from UEPA). UEAFTO has faced challenges in its daily operation regarding the feasibility of articulating teaching and assistance, in accordance with the premises of the SUS and the profile necessary for the future professional of this system. The Unit is a space for the production of knowledge and health care, in a dynamic process of evolution, with the potential to contribute even more to the training of qualified professionals to work in the SUS.